2021
DOI: 10.3390/cells10102543
|View full text |Cite
|
Sign up to set email alerts
|

Dual Inhibition of FAAH and MAGL Counteracts Migraine-like Pain and Behavior in an Animal Model of Migraine

Abstract: The endocannabinoid system exerts an important role in pain processing and modulation. Modulation of the system with hydrolase inhibitors of anandamide (AEA) or 2-arachidonyl glycerol (2-AG) has proved effective in reducing migraine-like features in animal models of migraine. Here, we investigated the effect of dual inhibition of the AEA and 2-AG catabolic pathways in the nitroglycerin-based animal model of migraine. The dual inhibitor JZL195 was administered to rats 2 h after nitroglycerin or vehicle injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 67 publications
8
28
1
Order By: Relevance
“…Reduction of c-Fos transcription was paralleled by a marked reduction in the expression of the genes encoding pronociceptive and proinflammatory peptides (CGRP, SP), proinflammatory cytokines (IL1-beta, IL-6, TNF-alpha), and nNOS. Lending support to the present data, a prior study had shown that the dual FAAH/monoacylglyceride lipase (MGL) inhibitor, which simultaneously blocks the degradation of AEA and 2-AG, lowers serum levels of CGRP in the same animal model of migraine [39].…”
Section: Discussionsupporting
confidence: 85%
“…Reduction of c-Fos transcription was paralleled by a marked reduction in the expression of the genes encoding pronociceptive and proinflammatory peptides (CGRP, SP), proinflammatory cytokines (IL1-beta, IL-6, TNF-alpha), and nNOS. Lending support to the present data, a prior study had shown that the dual FAAH/monoacylglyceride lipase (MGL) inhibitor, which simultaneously blocks the degradation of AEA and 2-AG, lowers serum levels of CGRP in the same animal model of migraine [39].…”
Section: Discussionsupporting
confidence: 85%
“…2-AG, 2-arachidonoylglycerol; AA, arachidonic acid; AEA, anandamide; Allosteric, allosteric ligands of the cannabinoid receptors; CBs, cannabinoid receptors; COX-2, cyclooxygenase-2; EA, ethanolamine; ECS, endocannabinoid system; FAAH, fatty acid amide hydrolase; Gly, glycerol; GPCRs, G-protein-coupled receptors; MAGL, monoacylglycerol lipase; NAAA, N-acylethanolamine acid amide hydrolase; OA, oleic acid; OEA, oleoylethanolamide; ORs, opioid receptors; OS, opioid system; PA, palmitic acid; PEA, palmitoylethanolamide; PG, prostaglandin; PPARs, peroxisome proliferator-activated receptors; TRPV1, transient receptor potential cation channel subfamily V member 1 [Color figure can be viewed at wileyonlinelibrary.com] seems straightforward, this topographically segregated effect of MAGL inhibition in trigeminal/extra-trigeminal areas warrants further research. Of interest, on the basis of our findings using the dual FAAH/MAGL inhibitor JZL195 in the NTG model,99 we recently suggested a synergistic role for anandamide and 2-AG in trigeminal pain modulation 100. This suggestion is in line with the report by Zubrzycki et al,98 which found that JZL195 modulated analgesia in an animal model of orofacial pain.…”
supporting
confidence: 86%
“…Furthermore, supplementation with GSE may protect against the development of a persistent pain state characteristic of chronic migraine since GSE was shown to inhibit sustained nociception in a chronic TMD model ( 13 ). Our findings provide further evidence to support an important role of CB receptors in modulating activity of the trigeminal system, which has been shown to involve suppressing nociception, repressing the stimulatory effects of CGRP, and inhibiting stimulated expression of proteins implicated in central sensitization in preclinical models of migraine ( 57 62 ). Although not a focus of this study, it is plausible that bioactive natural polyphenolic compounds present in GSE could bind to or modulate the endocannabinoid system to inhibit stress-induced sensitization of trigeminal neurons.…”
Section: Discussionsupporting
confidence: 65%